Passivação de superfícies de perovskitas via dopagem substitucional - Torres, Israel Silva (2023)
Humanity currently demands new energy sources to replace polluting energy sources and thus restructure the energy matrix in a sustainable manner. In this context, materials science plays a prominent role, as new materials enable the creation of sustainable and commercially viable energy sources. Perovskites have taken on a prominent role as light absorbers in photovoltaic cells by offering a low-cost alternative with superior optoelectronic properties, potentially surpassing current silicon-based technology. However, the application of these materials in solar energy conversion technology still faces various challenges in achieving competitive efficiency from a commercial perspective, and various enhancement strategies have been proposed. In particular, chemical surface passivation has shown promise in numerous experiments, but with many unexplored possibilities. In this doctoral thesis, we propose a novel surface passivation route through substitutional doping with trivalent cations. As a proof of concept, we apply our proposal to passivate the inorganic perovskite α-CsPbI3 on the (100) surface by replacing the Pb atoms occupying the surface octahedra with trivalent cations, namely In, Sb, and Bi. Our investigation employed ab initio simulation techniques based on density functional theory calculations.We found a preferential doping position in the surface octahedra with more than 0,35 eV/dopant compared to doping in deeper layers. We also observed a reduction in the band gap due to the addition of surface states, resulting in optical band gaps larger than the fundamental ones due to forbidden optical transitions (i.e., dark transitions). Among the dopants used, surface passivation with Bi atoms proved to be the most effective, with enhanced solar light absorption compared to the non-passivated α-CsPbI3 phase. Additionally, we varied the doping concentration and demonstrated the possibility of combining trivalent cations with other passivation mechanisms. Thus, our results for the specific case of α-CsPbI3 perovskite demonstrate the effectiveness of this doping proposal, pointing to a promising new route for improving the optoelectronic properties of perovskites in the field of photovoltaic applications.